Development of Wireless Piezofilm Sensor for Monitoring Vehicle Suspension System - Zulkifli, Muhamamad Zuhairy; Masron, Zaihasrah; Omarova, Saltanat A. (Universitas Negeri Padang, 2021)
The use of piezoelectric sensors in the data acquisition of vibration signal for monitoring systems on vehicles is a practical way to determine the performance of vehicle suspension systems (VSS). However, the transmission of vibration signal data through piezoelectric sensors still relies on conventional techniques, such as wires, which can cause problems in areas with limited space and pose a safety risk for moving vehicles. This study developed a wireless piezofilm sensor-based data acquisition device to monitor VSS using an Arduino microcontroller as a signal processor and a Bluetooth HC-05 module as a wireless communication link with a control terminal. The data acquisition process is carried out by measuring the electrical signal resulting from the vibration of the piezofilm sensor caused by the dynamic motion of the VSS operation. The signal data acquired from the car's body and lower arm was analyzed using the Fast Fourier Transform (FFT) analytical method for comparison. The results of the analysis show that the vibration increases with the increase of the car speed. It found that the vibration at the lower arm of the car is higher than the body part. It can conclude that the developed wireless piezofilm device is effective and capable of performing VSS monitoring.